2018
DOI: 10.1016/j.molcel.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Gcn4 Binding in Coding Regions Can Activate Internal and Canonical 5′ Promoters in Yeast

Abstract: Gcn4 is a yeast transcriptional activator induced by amino acid starvation. ChIP-seq analysis revealed 546 genomic sites occupied by Gcn4 in starved cells, representing ∼30% of Gcn4-binding motifs. Surprisingly, only ∼40% of the bound sites are in promoters, of which only ∼60% activate transcription, indicating extensive negative control over Gcn4 function. Most of the remaining ∼300 Gcn4-bound sites are within coding sequences (CDSs), with ∼75 representing the only bound sites near Gcn4-induced genes. Many su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(117 citation statements)
references
References 58 publications
15
101
1
Order By: Relevance
“…2). Our observations are in agreement with recent reports that demonstrate how Gcn4 binds frequently in coding regions and can activate transcription from internal promoters (Rawal et al 2018;Mittal et al 2017). This suggests that a signigicant fraction of the cryptic promoters are in fact alternative promoters, whose expression under standard conditions is restricted by the chromatin organization or the absence of a particular transcription factor.…”
Section: Discussionsupporting
confidence: 93%
“…2). Our observations are in agreement with recent reports that demonstrate how Gcn4 binds frequently in coding regions and can activate transcription from internal promoters (Rawal et al 2018;Mittal et al 2017). This suggests that a signigicant fraction of the cryptic promoters are in fact alternative promoters, whose expression under standard conditions is restricted by the chromatin organization or the absence of a particular transcription factor.…”
Section: Discussionsupporting
confidence: 93%
“…However, not all intragenic promoters that have been identified are active in spt6-1004. For example, a recent study showed that Gcn4 activates transcription from many intragenic sites (Rawal et al, 2018) and most of those are not activated in an spt6-1004 mutant. In addition to encoding N-terminally truncated proteins, intragenic promoters can play other types of regulatory roles, such as interference with normal gene expression (Kim et al, 2017;Xie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Promoter-proximal pausing of Pol II is common in higher eukaryotes, but it is not generally observed in yeast (Mayer et al 2017). In wild-type cells, Pol II levels are low at the promoter and high on the gene (elongating Pol II), with a well-resolved dip at the transcript termination site (TTS), and a peak just downstream from the TTS that sometimes trails into the next gene, corresponding to terminating Pol II (Cole et al 2014;Rawal et al 2018b). Pol II transcribes through the TTS, which refers to the mRNA cleavage site, where poly(A) is added and the mRNA is released.…”
Section: Rsc and Isw1/chd1 Have Opposite Effects On The Levels Of Elomentioning
confidence: 99%